2010
DOI: 10.1002/14651858.cd006507.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Meditation therapies for attention-deficit/hyperactivity disorder (ADHD)

Abstract: As a result of the limited number of included studies, the small sample sizes and the high risk of bias, we are unable to draw any conclusions regarding the effectiveness of meditation therapy for ADHD. The adverse effects of meditation have not been reported. More trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Among healthy adults, yoga's benefits in stress reduction have been shown in randomized controlled trials, but these studies had methodological flaws with short periods of intervention and limited follow-up data (Chong, Tsunaka, Tsang, Chan, & Cheung, 2011). Yoga's benefits have been shown in pediatric populations as well, although the small number of studies and methodological flaws make it difficult to draw definitive conclusions about the efficacy of yoga interventions with children (Krisanaprakornkit, Ngamjarus, Witoonchart, & Piyavhatkul, 2010).…”
Section: Yoga's Efficacy As a School-based Interventionmentioning
confidence: 99%
“…Among healthy adults, yoga's benefits in stress reduction have been shown in randomized controlled trials, but these studies had methodological flaws with short periods of intervention and limited follow-up data (Chong, Tsunaka, Tsang, Chan, & Cheung, 2011). Yoga's benefits have been shown in pediatric populations as well, although the small number of studies and methodological flaws make it difficult to draw definitive conclusions about the efficacy of yoga interventions with children (Krisanaprakornkit, Ngamjarus, Witoonchart, & Piyavhatkul, 2010).…”
Section: Yoga's Efficacy As a School-based Interventionmentioning
confidence: 99%
“…The last four protocols (75-78) examined non-pharmacological treatments for ADHD in children (acupuncture, parent training interventions, polyunsaturated fatty acids and social skills training), but were excluded because the protocols were not yet available in full review format. Therefore, three reviews (with a total of ten trials and 594 participants) met the inclusion criteria for this overview (55)(56)(57). Each included review examined a different intervention: family therapy (FT), homeopathy (Hom) and meditation therapy (MT).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…In recent years, nonpharmacological treatments for ADHD have been increasing in popularity as communities become aware of the potential dangers of stimulant use in children (51): between 50-68% of children with ADHD have tried one or more non-pharmacological therapies (52;53), and parents of children with ADHD tend to prefer non-pharmacological therapies for their children (54). Therefore, this overview examines evidence on the efficacy and safety of three nonpharmacological treatments for the management of ADHD in children: family therapy, homeopathy, and meditation therapy (55)(56)(57). These treatments have been compared to drug therapies, non-drug therapies and control conditions, and they have been studied using a variety of parent questionnaires, teacher questionnaires and child-completed psychological tests.…”
Section: Why It Is Important To Do This Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A Cochrane review found current research inadequate to suggest meditation for attention-deficit/ hyperactivity disorder and suggested additional trials. 81 Active-controlled RCTs and active-control programs of concentration meditation in children and youth have included both transcendental meditation (TM) and the relaxation response.…”
Section: Concentration Meditationmentioning
confidence: 99%